2017
DOI: 10.1177/2192568217716149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Perioperative Factors During Minimally Invasive Pre-Psoas Lateral Interbody Fusion of the Lumbar Spine Using Either Navigation or Conventional Fluoroscopy

Abstract: Study Design:Retrospective clinical study.Objectives:The aim of this study was to compare intraoperative conditions and clinical results of patients undergoing pre-psoas oblique lateral interbody fusion (OLIF) using navigation or conventional fluoroscopy (C-ARM) techniques.Methods:Forty-two patients (22 patients by navigation and 20 by fluoroscopy) underwent the OLIF procedure at 2 medical centers, and records were reviewed. Clinical data was collected and compared between the 2 groups. Patients were followed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Although there have been previous publications on OLIF and navigation, most of these papers did not specifically report cage placement accuracy. 5,6,27 However, Joseph et al, 7 Liu et al, 8 and Park 9 have previously reported navigation accuracy in LLIF surgery, and our findings are consistent with their previously reported accuracy rates. One issue, however, is the added radiation exposure to the patient with the second O-Arm spin for the pedicle screw fixation.…”
Section: A B Csupporting
confidence: 92%
See 3 more Smart Citations
“…Although there have been previous publications on OLIF and navigation, most of these papers did not specifically report cage placement accuracy. 5,6,27 However, Joseph et al, 7 Liu et al, 8 and Park 9 have previously reported navigation accuracy in LLIF surgery, and our findings are consistent with their previously reported accuracy rates. One issue, however, is the added radiation exposure to the patient with the second O-Arm spin for the pedicle screw fixation.…”
Section: A B Csupporting
confidence: 92%
“…2). 5 With regards to percutaneous screw fixation, the patient was subsequently positioned prone either on the same day or a subsequent date, depending on how extensive the surgery was. A reference arc was placed either in the iliac crest or on the spinous process, and another O-Arm spin was performed to register the navigation.…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…38 Adoption of CAN by spinal surgeons is further limited by concerns over temporal efficiency, particularly as a result of cumbersome registration workflow. 40 In a comparative study of O-arm (3-D CBCT) versus fluoroscopy guidance for MIS lateral interbody lumbar fusions, Zhang et al 41 demonstrated a statistically insignificant increase in operative time with CAN guidance. In larger in vivo studies, both Rajasekaran et al 42 and Tabaraee et al 43 found time-equivalence for 3-D CBCT-based navigation versus fluoroscopy for the placement of posterior thoracolumbar pedicle screws.…”
Section: Current Paradigm and Challengesmentioning
confidence: 99%